Analisis Kompetensi Audit, Opini Audit, Dan Ukuran Kap Terhadap Kredibilitas Profesi Audit Di Indonesia - Hernawan, Deby Indah Maharani; Machdar, Nera Marinda (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study critically explores the impact of auditor competence, audit opinion quality, and the size of the Public Accounting Firm (KAP) on the legitimacy of the audit profession in Indonesia, with corporate governance mechanisms as a potential moderating factor. A quantitative approach is applied through the utilization of secondary data sourced from the annual financial statements and audit documents of selected companies. The analysis technique involves multiple linear regression and Moderated Regression Analysis (MRA) to evaluate the interaction and moderating effects between variables in depth. The anticipated findings indicate that auditor competence, audit opinion integrity, and KAP reputation play crucial roles in strengthening the credibility of the audit profession, although this study acknowledges potential methodological limitations such as sample selection bias.